If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(8u+2)=3(2u+7)
We move all terms to the left:
2(8u+2)-(3(2u+7))=0
We multiply parentheses
16u-(3(2u+7))+4=0
We calculate terms in parentheses: -(3(2u+7)), so:We get rid of parentheses
3(2u+7)
We multiply parentheses
6u+21
Back to the equation:
-(6u+21)
16u-6u-21+4=0
We add all the numbers together, and all the variables
10u-17=0
We move all terms containing u to the left, all other terms to the right
10u=17
u=17/10
u=1+7/10
| 6+2(2u-1)=-5(2u-2)+6u | | 2n+2=3n+9 | | 13(4x-6)=23-6x | | 5=-6+x/3 | | 6+2(2u-1)=-5 | | 3(9-x)=6(x+6) | | (2x-60)+(3x+30)=180 | | 9/8=g+4/8 | | 4(7-n)=5n-8 | | -9.1(-7r-20)=-13 | | 3x=+4=-11 | | 3(y+2+2(y-3=15 | | 2(x5)-8=34 | | 12=y-5/4. | | Z+40=5z | | -9x+3=-10+10 | | -2h+4h=18 | | 120.5=5z. | | 0.15+23=0.19x | | t-7+3t=-2+4t-5 | | 5y-6=y+42 | | -2h+4=18 | | 3n2+7n=20 | | 6n+7=-20 | | 22=4K+7k | | 3i=-21 | | -2v9=25 | | 4x=84. | | -3x+-5=6 | | 12s-45=s+43 | | 460-45x=100 | | 2x-(3x-5)=4(-x-1) |